Enzymatic de Novo Pyrimidine Nucleotide Synthesis - Schultheisz, Heather L. (2010)
The use of stable isotope labeling has revolutionized NMR studies of nucleic acids, and there is a need for methods of incorporation of specific isotope labels to facilitate specific NMR experiments and applications. Enzymatic synthesis offers an efficient and flexible means to synthesize nucleoside triphosphates from a variety of commercially available specifically labeled precursors, permitting isotope labeling of RNAs prepared by in vitro transcription. Here, we recapitulate de novo pyrimidine biosynthesis in vitro, using recombinantly expressed enzymes to perform efficient single-pot syntheses of UTP and CTP that bear a variety of stable isotope labeling patterns. Filtered NMR experiments on (13)C, (15)N, (2)H-labeled HIV-2 TAR RNA demonstrate the utility and value of this approach. This flexible enzymatic synthesis will make implementing detailed and informative RNA stable isotope labeling schemes substantially more cost effective and efficient, providing advanced tools for the study of structure and dynamics of RNA molecules.